Spatial analysis of fast-food accessibility and obesity among adults in Malaysia nationwide - Kimberly Yuin Y’ng Wong; Foong-Ming Moy; Sanjay Rampal (PLoS ONE, 2025)
With the rising prevalence of obesity in Malaysia, addressing the obesogenic environment is increasingly urgent. While fast-food environments were linked to obesity and poorer diet quality in Western populations, evidence on this association in Malaysia remains limited. This study evaluated the association between accessibility to fast-food restaurants (FFR) and Body Mass Index (BMI) among adults aged 18–59 years from the National Health and Morbidity Survey (NHMS) 2015. After exclusions due to data requirements, 14,584 respondents from the initial 19,935 were included. FFR locations were obtained from websites of major franchises. Fast-food (FF) proximity was distance to the nearest FFR from each respondent’s residence. FF spatial access was the sum of inverted distances to all FFR within an 8 km Euclidean distance and subsequently categorized into none, low, moderate, and high. Multilevel linear regression adjusted the associations of BMI for socio-demographics, district population density, and district median income. Among the respondents studied (51.5% female), mean BMI was 26 kg/m 2 and median FF proximity was 2.6 km, where 77.3% had spatial access to at least one FF restaurant within 8 km from their residence. The overall association between FF proximity and BMI was not significant but modified by sex (p- heterogeneity <0.001). An exponential decrease in FF proximity was associated with 0.7 kg/m 2 (p < 0.001) increase in BMI among males and 0.4 kg/m 2 (p < 0.05) decrease among females. Compared to those with no FF access, males with Low, Moderate, and High FF access had higher BMI (0.6, 0.6, and 1.0 kg/m 2 , p -trend = 0.001), while females had lower BMI (−0.3, −0.6, and −0.9 kg/m 2 , p -trend < 0.001). The findings suggest that environmental exposures do not affect all population groups equally. Therefore, public health strategies and future research on obesogenic environments should consider the influence of social, cultural, and the broader environmental factors.